Islamic Identity and Foreign Policy Discourse: Indonesia’s Responses to the US War in Afghanistan (2001-2002) - Agus Salim (Studia Islamika, 2020)
Observers of Indonesia’s foreign policy commonly argue that while the state needs to include domestic Muslim interests in its foreign policy formulation, foreign policy officials have rarely considered Islam in their policy choices, with a dual-identity predicament constraining such a move. This article challenges this argument by demonstrating that foreign policy leaders have begun referring to Islamic identity and norms when justifying Indonesia’s foreign policy choices. By discussing Indonesia’s foreign policy responses to the United States’ war in Afghanistan in 2001, this paper elucidates the way in which Indonesia’s foreign policy leaders have constructed Islam as an “inclusive civilizational” identity in their foreign policy discourse, legitimizing their alliance with the global war on terrorism amid staunch domestic Muslim opposition to the war. They managed to turn identity constraint into opportunity by framing their policies within the context of “inclusive” and “integrative” Islamic values and norms.